Cinnamon oil as a co-chemotherapy agent through inhibition of cell migration and MMP-9 expression on 4T1 cells - Aliyah, Alma Nuril (De Gruyter Open Access, 2021)
Objectives: The long-term and high-dose use of doxorubicin as chemotherapy for triple-negative breast cancer (TNBC) patients induces epithelial-to-mesenchymal transition (EMT) and stimulates cancer metastasis. Cinnamaldehyde is a major compound of cinnamon oil (CO) suppressing Snail and NFκB activity that are involved in cell migration. This study aims to explore the activity of CO as a co-chemotherapeutic agent on 4T1 breast cancer cells. Methods: The CO was obtained by water and steam distillation and was characterized phytochemically by gas chromatography-mass spectrometry (GC-MS). Cytotoxic activity of single CO or in combination with doxorubicin was observed by MTT assay. Cell migration and MMP-9 expression were measured by scratch wound healing and gelatin zymography assays. The intracellular reactive oxygen species (ROS) levels were observed by 2′,7′–dichlorofluorescin diacetate (DCFDA) staining flowcytometry. Results: The phytochemical analysis with GC-MS showed that CO contains 14 compounds with cinnamaldehyde as the major compound. CO exhibited cytotoxicity on 4T1 cells with the IC50 value of 25 μg/mL and its combination with doxo-rubicin decreased cell viability and inhibited cell migration compared to a single use. Furthermore, the combination of CO and doxorubicin inhibited MMP-9 expression and elevated intracellular ROS levels compared to control. Conclusion: CO has the potential to be developed as a co-chemotherapy agent through inhibition of cell migration, and intracellular ROS levels elevation.